Pendampingan Implementasi Manajemen Risiko Covid-19 Di Tempat Beribadah - Herry Achmad Buchory; RR Rachmawati (Indonesian Community Service and Empowerment Journal (IComSE), 2021)
The world is currently in shock with the emergence of the corona virus known as COVID-19. The virus, which was first discovered in the city of Wuhan, China at the end of December 2019, spreads quickly and has spread throughout the world, including Indonesia. The increasing growth of the corona virus has spread to various aspects of life, from the economic field to the religious aspect. Muslims who usually carry out various congregational prayers freely in mosques are now no longer happening, even mosques are considered as one of the clusters for the spread of the Covid-19 virus. Considering these conditions, we are called to provide assistance in implementing risk management in mosques by providing knowledge and understanding about the importance of prevention and risk management efforts and providing the equipment needed to support the implementation of risk management in places of worship. By assisting the implementation of this risk management, the awareness of the congregation can increase through the implementation of carrying out risk management practices on a regular and sustainable basis so that the prevention of the spread of the Covid-19 virus can be suppressed and religious activities can continue.